The Impact of Corporate Governance on Customer Satisfaction and Loyalty of Islamic Insurance Company in Indonesia - Peni Nugraheni; Lia Fauziah (Journal of Accounting and Investment, 2019)
The implementation of the corporate governance in managing Islamic insurance companies hopefully can support the performance of companies to provide the best services for consumers in accordance with the Islamic principles. Good performance related to transparancy, independency, accountability,  responsibility, fairness and sharia compliance are expected to increase the trust of potential customers of Islamic insurance. This study aims to examine the impact of the corporate governance toward customer satisfaction and customer loyalty in Islamic insurance companies in Indonesia. A purposive sampling technique is used for this research. Using primary data through questionnaires to Islamic insurance customer, the research finds that corporate governance positively influence the customer satisfaction and customer loyalty. Another result reveals that the customer satisfaction positively influences customer loyalty. This study recommends the strengthening of corporate governance implementation to enhance the attractiveness of Islamic insurance company and give impact on customer satisfaction and customer loyalty.